Pelaksanaan Penilaian Kompetensi Sikap Sosial dalam Pembelajaran Daring Sosiologi di SMA Negeri 1 Sutera Pessel - Astari, Wahyuni; Junaidi, Junaidi (Naradidik: Journal of Education and Pedagogy, 2022)
Learning at SMA Negeri 1 Sutera Pessel is carried out online, so that the implementation of the assessment of the competence of social attitudes in learning sociology at SMA N 1 Sutera is carried out online. This study aims to describe the implementation of assessment of social attitudes in online learning of Sociology at SMA N 1 Sutera, Pesisir Regency South. This research was analyzed by the theory proposed by Parson (Laurer, 1982). This study uses a qualitative approach, the technique of selecting informants is purpose sampling, with the number of informants 13 people. Data collection is carried out by means of observation and interviews which are analyzed using data analysis techniques from Miles and Huberman. The results showed that the method of implementing sociology teachers in assessing social attitudes in online learning of Sociology at SMA N 1 Sutera, Pesisie Selatan Regency, A good assessment is carried out directly through offline meetings with non-test techniques, so that the results are truly in accordance with the actual situation. In fact, the assessment of social attitudes during the pandemic is carried out indirectly through online meetings. Even though the situation is not possible, teachers are still required to carry out the social attitude assessment process.